“Harus Tanding Dulu”: Konseling Guru al-Qur’an Hadis pada Peserta Didik Pelaku Kekerasan Fisik - Ardiansyah, Mochammad Zaka; Rona Mahdiyyah; Nurjihan Afifah Salsabila; Fitriyatul Hasanah (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2024)
Driven by the trend of implementing child-friendly Islamic education and the motivation from the Director-General of Primary and Secondary Education to optimize teachers’ roles as counselors, this article highlights best practices by religious subject teachers in counseling aggressive students involved in physical violence. The study involved Al-Qur'an Hadith teachers, the homeroom teacher of the offending student, and the counseling guidance teacher at Madrasah Tsanawiyah Al-Mubin as informants. The informants were purposefully selected using purposive sampling and interviewed through semi-structured interviews guided by a pre-prepared interview framework. The findings reveal that Al-Qur'an Hadith teachers employed directive counseling techniques, particularly probing and advice-giving, when counseling aggressive students involved in physical violence. Additionally, the teachers engaged in case conferences, conducted home visits, and built multi-stakeholder collaborations. These findings make a significant contribution to the field of Islamic religious education by demonstrating the active role of religious subject teachers in intervening with aggressive students through counseling.